Development of Video Media to Increase Dribbling Learning Result in a Sport Games - Nawawi; I Nyoman Sudana Degeng; Abd. Cholid (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2019)
Physical sports and healthy Education is one of the subjects that students like especially football game. Dribbling video media on football games is one of the solutions that are expected to motivate students to learn independently, creatively, effectively and efficiently. Therefore, it is necessary to develop the learning material of football game technique. technique to attract interest and reduce the saturation of learning in the students of class X Computer and Network Engineering (TKJ) which is designed interesting and specially designed in the form of CD media and dribbling technique skill manual on football game. Model development of dribbling video media learning on football game used is Dick and Carey model. Media video dribbling on the game of football and tested through 2 stages, namely (1) Expert test that is the review of the content experts / learning materials; learning media experts; and design experts, (2) Field test is individual group testing; small group trial; and large group trials. Based on the responses given by experted on dribbling video media on football games is like to use. Based on the responses given by the students of class X TKJ semester 2 as respondents to dribbling video media product on football game is feasible to be used by students of class X TKJ semester 2.